Biodiesel effects on transient needle motion and near-exit flow characteristics of a high-pressure diesel injector. (June 2014) - Moon, Seoksu; Tsujimura, Taku; Gao, Yuan; Park, Suhan; Wang, Jin; Kurimoto, Naoki; Nishijima, Yoshiaki; Oguma, Mitsuharu
In this study, biodiesel effects on transient needle motion and near-exit flow characteristics of a single-orifice high-pressure diesel injector were investigated in terms of needle-lift, needle speed, exit velocity and near-exit flow structure under various injection pressures. Ultrafast x-ray phase-contrast imaging technique was employed in this study to analyze the transient needle motion and near-exit flow characteristics. High-energy sub-nanosecond x-ray pulses have a potential to visualize the needle inside the nozzle and near-exit dense supersonic flow which speed reaches over 600 m/s. Transient needle motion and the structure and velocity of near-exit supersonic flows can be obtained by fabricated analysis of the x-ray images regardless of fuel, injection condition and type of injector. High bulk modulus and viscosity of biodiesel normally slow down the needle movement and decrease the flow performance. During opening-transient, sharp increase and following overshoot in needle speed and exit velocity were observed with a concurrent increase in spray width. The biodiesel showed a slower increase in needle speed, exit velocity and spray width but a higher degree of velocity overshoot during opening-transient. At steady-state, the biodiesel showed less turbulent flow structure and smaller spray width than diesel. During closing-transient, an abrupt increase in needle speed and decrease in exit velocity were observed with a concurrent increase in spray width. The biodiesel showed the retarded start of closing-transient and longer total injection duration under same energizing pulse duration. The difference between biodiesel and diesel became insignificant at low injection pressures roughly below 100 MPa.